2017
DOI: 10.12659/msm.902210
|View full text |Cite
|
Sign up to set email alerts
|

Total Oxidant/Antioxidant Status in Sera of Patients with Esophageal Cancer

Abstract: BackgroundOxidative stress parameters such as total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) have been studied in breast, thyroid, and simple esophageal cancers (EC). We evaluated these parameters in patients with EC and analyzed their correlations with treatment outcomes.Material/MethodSerum TOS, TAS, and OSI in 92 patients with EC at different clinical stages and in 64 healthy people (controls) were measured.ResultsSerum TOS, TAS, and OSI were significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The increase in the level of MDA and TOS in advanced group more than early group is perhaps due to excessive free radicals formation and lipid peroxidation occur due to the malignant interprets the utilization of existing antioxidant system for defending the additional oxidative stress. Huang et al (2017) measured serum TOS, TAS, and OSI in patients with esophageal cancer and healthy controls and were all significantly different, but they found no significant differences across different clinical stages in the cancer group.…”
Section: Discussionmentioning
confidence: 93%
“…The increase in the level of MDA and TOS in advanced group more than early group is perhaps due to excessive free radicals formation and lipid peroxidation occur due to the malignant interprets the utilization of existing antioxidant system for defending the additional oxidative stress. Huang et al (2017) measured serum TOS, TAS, and OSI in patients with esophageal cancer and healthy controls and were all significantly different, but they found no significant differences across different clinical stages in the cancer group.…”
Section: Discussionmentioning
confidence: 93%
“…[18] Furthermore, the relationship between different malignancies with TOS and TAC levels was investigated in a great number of studies. [19][20][21] TOS and OSI index were found higher in esophageal cancer patients compared to controls. [21] Moreover, these biomarkers were reported to be candidates in the diagnosis of esophageal cancer.…”
Section: Discussionmentioning
confidence: 75%
“…[19][20][21] TOS and OSI index were found higher in esophageal cancer patients compared to controls. [21] Moreover, these biomarkers were reported to be candidates in the diagnosis of esophageal cancer. [21] On the other hand, authors demonstrated no correlation between stage of cancer and TOS levels.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations